Pengaruh Pandemi Covid-19 terhadap Return Saham pada Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI - Hendi Farnijab; Zulkifli Umar; Budi Safatul Anam (AKUNTANSI 45, 2026)
The purpose of this study is to examine the effect of profitability and liquidity on the firm value of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2021. This research employed a quantitative comparative method to identify differences in company performance, particularly stock returns, before and during the Covid-19 pandemic. Purposive sampling was applied to select 31 pharmaceutical sub-sector companies that met the predetermined criteria as the research sample. The data used in this study were secondary data obtained from published financial reports and official IDX sources. Data analysis was conducted using simple linear regression supported by descriptive statistical analysis. The findings indicate that there is a significant difference in stock return variables between the period before and during the Covid-19 pandemic. In addition, the analysis describes the maximum, minimum, and average values of the research variables across the 31 pharmaceutical sub-sector companies during the observed period. Based on the results and discussion, it can be concluded that the Covid-19 pandemic has a measurable impact on stock returns of pharmaceutical sub-sector companies listed on the IDX during 2019–2021.